Efek Mediasi Dukungan Sosial terhadap Religiusitas dan Resiliensi Mahasiswa Santri selama Pandemi COVID-19 - Fauzul Adim Ubaidillah; Suryanto Suryanto; Dyan Evita Santi (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
This study aims to examine the relationship between religiosity and resilience and the role of social support as a mediating variable. This study used correlational quantitative method. There were 367 participants who were selected based on the cluster random sampling technique. Data analysis used mediation regression analysis. The results showed that religiosity has a positive and significant relationship with resilience and social support has a role as a partial mediator in the relationship between religiosity and resilience. Resilience development can be done by developing religiosity as an individual psychological resource accompanied by the provision of social support by religious institutions as an external resource.